2022
DOI: 10.3389/fsufs.2022.788939
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Supernatant Obtained From a Salt Tolerant Bacillus amyloliquefaciens Strain Enhances Germination and Radicle Length Under NaCl Stressed and Optimal Conditions

Abstract: Seed germination and early plant growth are key stages in plant development that are, susceptible to salinity stress. Plant growth promoting microorganisms (PGPMs) produce substances, in their growth media, that could enhance plant growth under more optimal conditions, and or mitigate abiotic stresses, such as salinity. This study was carried out to elucidate the ability of a NaCl tolerant Bacillus amyloliquefaciens strain's cell-free supernatant to enhance germination and radicle length of corn and soybean, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…A decrease in the hydrolase enzyme class representation by 94% ( Table 2 ), as reported here, suggested that some of the enzymes, such as the proteases, which are normally extracellular with a good stability, were not functional [ 69 , 70 ]. Furthermore, bacteria of the Bacillus genus are known for their commercial production of proteases, especially neutral and alkaline ones [ 71 ], which, again, is reflected in the current study in the greater representation of the hydrolase enzyme class at both pH 7 and 8. Some microbes induce components of the Clp protease complex to participate in protein homeostasis by removing the damaged/degraded proteins.…”
Section: Discussionmentioning
confidence: 77%
“…A decrease in the hydrolase enzyme class representation by 94% ( Table 2 ), as reported here, suggested that some of the enzymes, such as the proteases, which are normally extracellular with a good stability, were not functional [ 69 , 70 ]. Furthermore, bacteria of the Bacillus genus are known for their commercial production of proteases, especially neutral and alkaline ones [ 71 ], which, again, is reflected in the current study in the greater representation of the hydrolase enzyme class at both pH 7 and 8. Some microbes induce components of the Clp protease complex to participate in protein homeostasis by removing the damaged/degraded proteins.…”
Section: Discussionmentioning
confidence: 77%
“…NaCl stress is a major global constraint to food production ( Naamala and Smith, 2021b ). Plant growth promoting microorganisms (PGPM), or their derived compounds have been reported to enhance plant growth under saline conditions ( Schwinghamer et al, 2016 ; Subramanian et al, 2016a , b ; Ilangumaran et al, 2021 ; Naamala et al, 2022 ). However, use of microbial CFS as plant growth biostimulants is less explored, with just a handful of publications available ( Tewari et al, 2020 ; Shah et al, 2022 ; Naamala et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two NaCl levels, (100 mM NaCl and 150 mM NaCl) and two CFS levels (1.0 and 0.20% [v/v]) were used in the mixtures to formulate treatments. The two CFS concentrations were chosen because they exhibited positive results with Bacillus amyloliquefaciens EB2003 CFS, in our previous study ( Naamala et al, 2022 ). 0, 100 and 150 mM NaCl, with no addition of CFS were used as negative controls.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations